Pengaruh Kompetensi dan Motivasi terhadap Kinerja Karyawan Kelurahan Banjarsugihan Kecamatan Tandes Kota Surabaya - Purwati, Tri Indah (Ridwan Institute, 2025)
This study aims to examine and analyze the influence of competence and work motivation on employee performance at Banjarsugihan Urban Village, Tandes District, Surabaya City. The research adopts a quantitative approach with purposive sampling technique to select a total of 50 respondents. Data were collected through questionnaires and analyzed using simple linear regression and multiple linear regression with the assistance of SPSS software. The results show that competence does not have a positive and significant effect on employee performance, indicating that improved employee competence has not yet become a key determinant of performance. In contrast, work motivation has a positive and significant influence on employee performance, suggesting that a high level of motivation encourages employees to work more optimally. The results of this study also indicate that competence and work motivation simultaneously have a significant effect on employee performance. These findings indicate that both competence and work motivation are important factors to consider in human resource management within public service environments such as urban villages, in order to improve employee performance effectiveness and efficiency. Therefore, it is recommended that the management of Banjarsugihan Urban Village continue to enhance programs for competence development and work motivation to achieve better and more sustainable employee performance.